Environmental Adaptability Assessment of FiberReinforced Composites based on Fuzzy Comprehensive Evaluation Method. Issue 4 (January 2021) - Chen, Y; Huang, H Z; Qiao, Z P; Yang, W J; Chen, X H; Luo, D; Qin, Y J; Wu, S
Abstract: The environmental adaptability of fiber reinforced composites is affected by different environmental factors. By recording the environmental factors parameters and performance parameters related to the test environment, the main parameters affecting the material properties are obtained by gray correlation analysis on the environmental factors parameters; the main environmental factors affecting the material performance are selected, and the weight of environmental factors is determined by AHP According to the characteristics of environmental factors, a membership function is constructed to evaluate the environmental adaptability of materials when the main parameters of environmental factors are known. At the end of this paper, the effectiveness of the environmental adaptability evaluation method is verified by the test results of similar fiber reinforced composite materials.